The relationship among idiosyncratic deals, psychological empowerment, and internal locus of control: A moderated mediation model - Shams, Muhammad Shahid; Mei, Tang Swee; Adnan, Zurina; Niazi, Murtaza Masud; Khan, Kaleemullah (Frontiers in Psychology, 2022)
Building upon the JD-R theory, this research offers an in-depth exploration of the mechanisms by which idiosyncratic deals, such as personalized work arrangements, can enhance academics’ psychological empowerment and hence affect their work engagement. This study’s purpose was to investigate whether psychological empowerment mediates the relationships between task and work responsibilities Ideals, flexibility I-deals, and work engagement among academics in higher education and whether the mediating effects are moderated by academics’ internal locus of control. Using an online platform, the survey questionnaire was sent to 650 academics working in higher education. Results reveal that task and work responsibilities I-deals and flexibility I-deals are positively associated with the academics’ work engagement and that psychological empowerment mediates those relationships. Additionally, the internal locus of control strengthens the positive relationship between task and work responsibilities I-deals and psychological empowerment, and it enhances the indirect effect of task and work responsibilities I-deals on academics' work engagement through psychological empowerment. Though, this study did not find the moderating effect of internal locus of control on the flexibility I-deals-psychological empowerment relationship; however, results indicate that internal locus of control boosts the indirect effect of flexibility I-deals on academics' work engagement through psychological empowerment.